Enhancement of flow boiling using 3D printed porous structures - Wang, Yawei (2016)
With the ever-increasing density and compactness of microprocessors on a chip, the heat generated by these electronic units rises along. The rate of heat dissipation has become a limiting factor in the performance of the chips and hence, it is of vital importance that efforts in searching for effective methods of cooling continue so that the electronic components could be used to their maximum capacity. In this project, an experimental investigation was carried out to study the effect of coolant mass flux, porous structure modification and unit cell size of substrate on flow boiling heat transfer. Experiments were conducted on five different substrates of three distinct structures fabricated by 3D printing, which function as the heat sink. During each experiment, the substrate was inserted in a rectangular evaporator channel where heat was channelled vertically upwards with the use of dielectric coolant FC-72 for testing. The mass flux was varied from 6.5 to 13.5 kg/m2·s corresponding to the range of flow rate from 0.3 to 0.6 L/min while the heat flux was altered from 5.5 to 74.5 W/cm2. For each experiment, the wall temperature and coolant pressure were monitored, recorded and analysed to obtain the superheat and heat transfer coefficient of flow boiling at various heat power settings. From the experimental results, a higher coolant mass flux was seen to enhance heat transfer for both the empty channel and porous substrates tested to varying extents. Compared to the empty channel, all three porous structures improved cooling performance with "Spherical", "Octet" and "Dope" achieving 55.8%, 44.2% and 27.2% enhancement, respectively. Substrates with unit cell size 10 mm outperformed their ii counterparts of the same structure but of smaller unit cell size 5 mm by 10.0% and 4.5% for "Octet" and "Dope", respectively. The effect due to unit cell size was not as significant as other factors such as coolant mass flux and structure modification.